AB0610 No changes in sirtuin-1 (hdac 3) activity from pbmc of patients with osteoporosis. (23rd January 2014) - Wendling, D.; Godfrin-Valnet, M.; Khan, K.; Guillot, X.; Abbas, W.; Baud, L.; Toussirot, E.; Cedoz, J.-P.; Prati, C.; Herbein, G.
Abstract : Background: Sirtuin 1 (Sirt1) is a nuclear enzyme from the class 3 histone deacetylases (HDACs) modulating gene expression, involved in the regulation of diverse biological processes ( cell survival, apoptosis, gluconeogenesis, adipogenesis, lipolysis), local and systemic inflammation, as well as in bone and cartilage remodeling. Objectives: The main objective of the study was to evaluate Sirt1 activity in PBMC by venous blood aspiration in patients with osteoporosis (OP), compared to those of control patients, and to analyze the relationship between Sirt1 activity and production of mediators of inflammation and cytokines (TNFalpha, IL-6, IL-8) by the cells after ex vivo treatment with a Sirtuin activator, resveratrol, the most potent natural compound able to activate Sirt1. Methods: A prospective and comparative monocentric study was performed in order to compare the activity of Sirt1 in patients with OP and controls. OP was defined by low BMD and at least one vertebral fracture. Secondary causes of osteoporosis were ruled out. PBMC were isolated from venous blood, and Sirt1 activity was evaluated from cytoplasmic and nuclear compartments using a fluorometric assay (SIRT1 fluorometric kit, BML-AK-555, Enzo Life Sciences, Villeurbanne, France) at the 15 minutes point. Culture supernatant levels of TNF alpha, IL-6, IL-8 were quantified before and after resveratrol ( 1 µmol and 5 µmol) ex vivo treatment, with commercial kits (Quantikine Kits, R&D Systems, Minneapolis, MN). Bone remodeling markers (Ca, P, Vitamin D, sCTX I), and inflammation (CRP, ESR) were evaluated at the same time. Statistical analysis used Wilcoxon and t tests; significance : p less than 0.05. Results: Eighteen patients with symptomatic OP (age 68 ± 9 years) and 18 controls (age 54 ± 13 years) were included. No differences were found in cytoplasmic or nuclear Sirt1 activity between patients and controls. Cytoplasmic and nuclear Sirt1 activity were significantly correlated in patients and controls. Sirt1 activity did not correlate with bone biologic remodeling biomarkers or biologic markers of inflammation (CRP). After resveratrol treatment, no changes in TNF alpha, IL-6 or IL-8 levels were found, compared to pre treatment values, or between patients and controls. Conclusions: Sirt1 activity (cytoplasmic and nuclear) from PBMC was not different between OP patients and controls. These results suggest that there is no implication of Sirt regulation of pro inflammatory cytokines or chemokines in PBMC from patients with osteoporosis. Disclosure of Interest: None Declared